(untitled) (Carte Romanze, 2018)
Il contributo indaga la visione della regalità e i legami con i miroir aux princes coevi nell’opera di Watriquet de Couvin. All’interno di questa, sono stati selezionati quei testi dedicati esplicitamente all’educazione dei príncipi e perciò definibili come dits de la régalité. Dopo una disamina dedicata agli aspetti pedagogici e alle conseguenti disposizioni strutturali, il contributo procede a definire l’immagine del principe ideale cosí come si palesa dai testi, mettendo in rilievo i legami con la storia politica coeva. L’ultima parte, invece, è dedicata a un’indagine sulle possibili fonti dei dits de la régalité. This paper examines the point of view on royalty in the works of Watriquet de Couvin and the links with the contemporary miroirs aux princes. Watriquet’s works are eminently educational and moralistic. Among these, the paper selects the texts explicitly dedicated to the education of the princes and that can be labelled as dits de la régalité. After a discussion about the pedagogical aspects and the consequent structural aspects, the paper defines the image of the ideal prince revealed by the texts, highlighting the links with the contemporary political history. The last part, instead, is dedicated to an examination on the sources of the dits de la régalité.